Circular land use management in cities and urban regions - a policy mix utilizing existing and newly conceived instruments to implement an innovative strategic and policy approach. - Preuß, Thomas; Ferber, Uwe (My University, 2008)
Die Nationale Nachhaltigkeitsstrategie der Bundesregierung setzt auf die flächenpolitischen Ziele der Reduzierung der Flächeninanspruchnahme von derzeit etwa 100 Hektar auf 30 Hektar pro Tag und strebt die Realisierung eines Verhältnisses von Innen- zu Außenentwicklung von 3 zu 1 bis zum Jahr 2020 an. Für die Umsetzung einer hierfür erforderlichen Doppelstrategie aus Mengen- und Qualitätssteuerung ist die Flächenkreislaufwirtschaft ein zentraler Politik- und Strategieansatz. Die Flächenkreislaufwirtschaft verfolgt vorrangig und systematisch die Ausschöpfung von Potenzialen der Bestandsentwicklung und der Wiedernutzung von Brachflächen. Unter bestimmten Voraussetzungen lässt sie eine geringfügige Flächeneuausweisung zu. Sie zielt somit sowohl auf die Verminderung von Flächenneuausweisungen auf der grünen Wiese als auch auf die Mobilisierung von Bauland im Bestand. Für eine Realisierung der Flächenkreislaufwirtschaft müssen bestehende und neue Instrumente in den Handlungsbereichen Planung, Information, Organisationund Kooperation, Fördermittel und Budget, Vermarktung und Anordnungen in einem Policy-Mix gebündelt eingesetzt werden. Da das Zielerreichungspotenzial bestehender Instrumente begrenzt ist, sind neue Instrumente mit zieladäquaten Anreizen notwendig, die sowohl die bestehende Flächennutzung als auch die Flächenneuausweisung wirksam beeinflussen können. Der Bund und weitere Akteursgruppen sollten zukünftig eng bei der Schaffung geeigneter Rahmenbedingungen für eine Flächenkreislaufwirtschaft zusammenwirken. difu

The German government's National Strategy for Sustainable Development aims at reducing land utilization from the 100 ha per day currently used today to 30 ha a day and at realizing three times as much internal development as external development by the year 2020. Circular land use management is a key policy and strategic approach for implementing the two-pronged strategy of quantity and quality management necessary to achieve these objectives. Circular land use management primarily focuses on systematically exploiting the potentials of existing structures and reusing derelict land. It allows for zoning of new land for development on a small-scale under certain conditions. Consequently, this strategy endeavours to diminish new development in green belts and to activate previously developed building land. Realizing a Circular land use management policy requires employment of a policy mix which pools existing and new instruments in the fields planning, information, organization and cooperation, funding and budgeting, marketing and dispositions. New instruments which provide goal-oriented incentives capable of effectively influencing current land use and zoning practices are necessary because existing instruments have limited potential with regards to achieving these aims. The German government and other important groups of stakeholders the Länder, public stakeholders at the municipal and regional levels, private enterprise, institutions which own land, the real estate industry and private households and small-scale property owners should cooperate closely to establish appropriate framework conditions for Circular land use management. difu
Keywords: Flächennutzung; Flächennutzungsplanung; Flächenverbrauch; Siedlungsentwicklung; Planungsinstrument; Planspiel; Umweltschutz; Stadtplanung; Regionalplanung; Kreislaufflächenwirtschaft; Flächenmanagement; Flächenpolitik; Steuerungsinstrument; Flächenrecycling; Flächeneinsparung; Nachhaltige Entwicklung